Dengue and falciparum malaria co-infection in travelers returning from Burkina Faso: Report of two cases in Northeastern Italy - Antonio Mastroianni; Caterina Vocale; Vittorio Sambri; Tiziana Lazzarotto; Paolo Gaibani; Giada Rossini; Stefania Varani (Asian Pacific Journal of Tropical Medicine, 2023)
Rationale: Malaria and dengue are the most prevalent vector-borne diseases in tropical countries. Plasmodium parasite and dengue virus (DENV) concurrent infection is possible and often under-recognized in geographical areas where these infections are both endemic. Patients concern and diagnosis: We describe the first two cases of Plasmodium falciparum and DENV-3 co-infection in travelers returning to northeastern Italy from Burkina Faso during 2013-2014. Interventions: Malaria infection in both patients was treated with mefloquine. Due to the persistence of symptoms despite of the antimalaria treatment, dengue was also investigated; the treatment of dengue was symptomatic. Outcomes: The patients were discharged in good general condition. Lessons: The need for surveillance of potential malaria and dengue co-infection in travelers returning to Europe from endemic areas is highlighted, as infection with Plasmodium does not exclude arboviral co-infection.